University-Society Relationships: Institutional Barriers to the Effective Implementation of the University’s Third Mission in Tanzania - Gabriel Kanuti Ndimbo; Samwel Mashinya Nkwabi (SAGE Open)
In the past few decades, the roles and missions of universities have evolved from traditional missions of teaching, research, and publication to engaging directly in solving day-to-day societal problems and contributing to economic development. The increasing demands of the knowledge-based economy and globalization have played a significant role in transforming university roles. However, the third mission of universities is highly neglected in many universities compared to teaching, research, and publication. This study employs a qualitative approach to explore institutional barriers hindering the effective implementation of the universities’ third mission in Tanzania. The researchers carried out semi-structured and key-informant interviews with the members of the academic staff and administrative personnel from the three universities. Although all the respondents admitted that the university’s third mission is crucial in building solid university-society synergies and promoting local and regional development, its implementation is less prioritized in many universities than traditional university missions. The study revealed six main institutional barriers to implementing the universities’ third mission, ranging from (i) inadequate financial resources, (ii) work overloads for academics, (iii) lack of comprehensive institutional policies and regulations, (iv) lack of strong linkage between research and third mission, (v) barrier on incentives and reward systems for best practices, and (vi) barriers in capacity building for effective implementation of third mission. The study concludes that the university’s third mission is crucial in this competitive world. It helps universities and academic staff members brand themselves to the community and build strong synergies between the university and society.